2012
DOI: 10.1007/s11606-012-2208-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Events with Clopidogrel: A Nationwide Population-Based Cohort Study

Abstract: BACKGROUND: Clopidogrel prevents cardiovascular events, but has been linked with adverse gastrointestinal (GI) complications, particularly bleeding events. OBJECTIVE: We aimed to investigate the risk of adverse GI events in patients treated with clopidogrel. DESIGN: A nationwide population-based cohort study based on linkage of three administrative registries in Denmark. PARTICIPANTS: All individuals who redeemed at least one prescription of clopidogrel from 1996 to 2008 were included as exposed subjects (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…Similarly to our study, Grove et al 21 highlighted GI adverse events associated with clopidogrel in a nationwide Dutch population-based cohort. Their results suggested an NNH ranging from 33 to 58 patients.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly to our study, Grove et al 21 highlighted GI adverse events associated with clopidogrel in a nationwide Dutch population-based cohort. Their results suggested an NNH ranging from 33 to 58 patients.…”
Section: Discussionsupporting
confidence: 84%
“…However, the mono-or dual prescription option is subjective to the high risk of gastrointestinal hemorrhage, peptic ulceration, perforation and obstruction [9] [45]. The largest study done so far for patients treated with clopidogrel concluded that, clopidogrel use is associated with an increased risk of adverse gastrointestinal (GI) events such as gastritis, ulcers and bleeding, suggesting that the benefits of clopidogrel should be weighed up against an increased GI adverse risks [46]. However, given the risks of morbidity and death in patients on dual antiplatelet therapy, an expert consensus board recommends the use of proton pump inhibitors in dual antiplatelet therapy in patients who have higher risk factors for gastrointestinal bleeding [47] [9].…”
Section: ) Interaction Between Cyp3a4/3a5 and Its Alleles On Major Cmentioning
confidence: 99%
“…However, the mono-or dual prescription option is subjective to the high risk of gastrointestinal hemorrhage, peptic ulceration, perforation and obstruction [9,44]. The largest study done so far for patients treated with clopidogrel concluded that, clopidogrel use is associated with an increased risk of adverse gastrointestinal (GI) events such as gastritis, ulcers and bleeding, suggesting that the benefits of clopidogrel should be weighed up against an increased GI adverse risks [45]. However, given the risks of morbidity and death in patients on dual antiplatelet therapy, an expert consensus board recommends the use of proton pump inhibitors in dual antiplatelet therapy in patients who have higher risk factors for gastrointestinal bleeding [46,9].…”
Section: Allelic Distribution and Clopidogrel Responsiveness On Clinimentioning
confidence: 99%